Protein Expression of PI3K/AKT/mTOR Pathway Targets Validated by Gene Expression and its Correlation with Prognosis in Canine Mammary Cancer - Perossi, Isabela F. S. [UNESP]; Saito, Mylena M.; Varallo, Giovanna Rossi; de Godoy, Bianca Lara Venâncio; Colombo, Jucimara; Zuccari, Debora A. P. C. (Springer Nature, 2022)
Mammary cancer is the main type of neoplasia in female dogs and is considered an adequate model for the biological and therapeutic study of cancer in women. The PIK3CA/AKT/mTOR pathway plays a central role in cellular homeostasis and is often dysregulated in cancer. The increased expression of PI3K protein in the literature is associated with a poor prognosis, and alterations in the PIK3CA gene can lead to changes in downstream pathways. Thus, the objective of this study was to validate the protein expression to confirm the gene expression of proteins belonging to the main pathway PI3K and PTEN, and their downstream pathways through ZEB1, ZEB2, HIF1A, VHL, CASP3 and PARP1 relating to prognosis in canine mammary cancer. For protein studies, the samples came from 58 female dogs with mammary neoplasia, immunohistochemistry was performed and its analysis by the histoscore method. For the genetic evaluation, the samples came from 13 patients, the DNA was extracted and the analysis for quantitative expression. Through immunohistochemistry, PI3K positivity was significantly associated with affected regional lymph node, distant metastasis, patients with HER2+, Triple Negative and Luminal B phenotypes, and the lowest survival rates. Through gene expression, we observed higher gene expression of ZEB2 and PARP1 both among patients who were alive and who died, which was not true for the expressions of PIK3CA and HIF1A. In conclusion, the data observed in this work are promising in the study of new molecular prognostic markers such as PI3K, ZEB2 and PARP1 for canine mammary cancer.
Keywords: Angiogenesis; Apoptosis; H1047R; Mammary cancer; Metastasis